Use of Streptozotocin to Investigate the Effect of 6-paradol Nanoparticles on Sexual and Hormonal Markers in Diabetic rats: Use of Streptozotocin to Investigate the Effect of 6-paradol Nanoparticles on Sexual and Hormonal Markers in Diabetic rats Sci. - Abdullah, Jasim A.; Al-Mayali, Hussein K.; Hassan, Ahmed J. (Scientific Journal of Medical Research, 2022)
Objectives: The study aimed to explore the effect of 6-paradol nanoparticles in the therapy of changes in body weight, testis, and epididymis in male rats caused by Streptozotocin. Methods: : In diabetic rats, different concentrations of 6-paradol nanoparticles (20 mg and 40 mg/kg) were employed as a treatment for 60 days in several hormonal and histological parameters. The criteria evaluated were body weight, testis and epididymis weight, and the concentration of sex hormones (LH, FSH, and testosterone) in Rattus norvegicus produced by Streptozotocin. Results: The results showed a significant decrease in body weight and weight of testis and epididymis, as well as a decrease in testosterone, LH, and FSH concentrations, and a significant decrease in sperm concentration, motility, and viability, but an increase in the percentage of abnormal sperms in the STZ (G3) group of rats, but a significant increase in the weight of 6-paradol nanoparticle (G4&G5) group of rats. Conclusion: : Because of its efficacy in treating the testis and epididymis, and because it is also useful as an antibiotic or antioxidant, we can consider 6-paradol a very good substance. It is very safe on the body and has a nanometer-sized size that allows it to enter the cell and produce good results easily.